The Influence of Gadget use on Sexual Behavior of Adolescents in Class X SMAN 1 Palangka Raya City - Lita Lita; Melisa Frisilia; Stefanicia Stefanicia (PROMOTOR, 2026)
Background: Advances in digital technology have a major impact on the lifestyle of adolescents, especially in the use of gadgets. Gadgets provide easy access to information, including age-inappropriate sexual content. This phenomenon has led to an increase in teenage sexual behavior such as holding hands, hugging, kissing, and premarital sexual intercourse. The lack of sex education and parental supervision makes teenagers more vulnerable to the negative influence of gadgets. Objective: To determine and analyze the influence of gadgets use on the sexual behavior of class X adolescents at SMAN 1 Kota Palangka Raya. Methods: This study used an analytic quantitative approach with a Cross-Sectional design. A sample of 85 students was taken using total sampling technique. Data collection was done using a closed questionnaire. Data were analyzed using the Chi-Square test to see the influence between variables. Results: The statistical test results showed a P-value of 0.028 <0.05, which means there is a significant influence between the use of gadgets and adolescent sexual behavior at SMAN 1 Kota Palangka Raya. Conclusion: There is a significant influence between gadgets use and adolescent sexual behavior. Therefore, active involvement from parents, teachers, and public health workers is needed to provide education and supervision of gadgets use by adolescents to prevent risky sexual behavior.